BIOCONVERSION OF LIGNOCELLULOSIC MATERIALS WITH THE CONTRIBUTION OF A FERULOYL ESTERASE HYDROLASE FROM Alternaria tenuissima TO RELEASE CARBOHYDRATES - Dinh Giap, Vu; Dinh Duy, Vu; Van Thang, Bui (Journal of Forestry Science and Technology, 2022)
Feruloyl esterase catalyze the hydrolysis of a wide variety of glycosidic linkages between two or more carbohydrates or between a carbohydrate and a non-carbohydrate moiety. Thereby, they play a role in the initial degradation of lignocelluloses, which may be advantageous for the efficient degradation of the plant cell-wall complex that contains both diverse sugar residues and esterified structures. The contribution of the enzyme AltFAE was purified from Alternaria tenuissima to the conversion of lignocellulosic materials without any chemical pretreatment to release the carbohydrates, was studied. It was determined the activity of feruloyl esterase (AltFAE) production by A. tenuissima in liquid cultures with potential inducing agents sawdust, rice straw, tomato, potato, soybean, and corn starch. At the applied concentrations of soybean (2%), the highest levels ~ 689 U L-1 of enzyme activities were obtained. The disintegrating effect of enzymatic lignocellulose treatment can be significantly improved by using different kinds of hydrolytic and oxidizing enzymes. Synergistic conversion of cane bagasse also resulted in a release of 18.4 mg g-1 total carbohydrates (galactose, glucose, mannose, and xylose) per gram substrate using an “enzyme cocktail” [Cell/Xyl 50 U gds-1, AltFAE 10 U gds-1, and Lac 15 U gds-1] after incubating for 48 hrs at 45oC. The information presented in this paper is helpful to better understand the bioconversion of lignocellulosic materials with the contribution of a feruloyl esterase hydrolase from A. tenuissima to release carbohydrates.